Delirium Care Bundle On Sedation And Orientation Among Icu-Acquired Delirium A Randomized Controlled Trial (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Early identification of delirium symptoms and implementation of ABCDEF bundle among mechanically ventilated patients has been demonstrated as feasible, safe, and effective to reduce intensive care unit acquired delirium however it is most effective when it is delivered with the coordination of nursing staff and other health care team members. Objective: Aim of the study is to determine the effectiveness of a delirium care bundle on sedation and orientation among ICU-acquired delirium patients with mechanical ventilation. Materials and methods: Randomized controlled trial was conducted to implement a delirium care bundle. This intervention has been implemented daily for the seven days of ICU admission. Data were collected using the standardized Richmond Agitation and Sedation Scale to assess the level of sedation. A structured scale was developed by the investigator to assess the level of orientation. Statistical analysis was done by using SPSS 16.0 version. Results: The statistical mean scores revealed that there is a significant reduction in the level of sedation from day 1 to day 7 in the experimental group. (0.04 ± 1.42 to 1.00± 0.00) then the control group (7 0.61 ±1.49 to 1.04 ± 0.74). The level of orientation statistical mean scores shows that there is a significant improvement from day 1 to day 7 in the experimental group (1.00 ± 0.00 to 3.71 ± 0.46) than the control group (1.00 ± 0.00 to 2.14 ± 0.44). There is an overall effect of the delirium care bundle intervention on reducing the level of sedation (t(54)=-1.900, p=0.001*) and improving the level of orientation (t(54)=12.94,p=0.001*) among intubated ICU acquired delirium patients. Conclusion: Delirium care bundle intervention has been marked to significantly reduce agitation, and irritability, implementation of non-pharmacological pain management can lead to early orientation and ambulation. Nurses play a significant role in identifying the risk factors, and symptoms of delirium at the initial stage.